Defining Patient Engagement in Research: Results of a Systematic Review and Analysis: Report of the ISPOR Patient-Centered Special Interest Group - Harrington, Rachel L.; Hanna, Maya L.; Oehrlein, Elisabeth M.; Camp, Rob; Wheeler, Russell; Cooblall, Clarissa; Tesoro, Theresa; Scott, Amie M.; von Gizycki, Rainald; Nguyen, Francis; Hareendran, Asha; Patrick, Donald L.; et al. (Value in health, 2020)
Lack of clarity on the definition of “patient engagement” has been highlighted as a barrier to fully implementing patient engagement in research. This study identified themes within existing definitions related to patient engagement and proposes a consensus definition of “patient engagement in research.” A systematic review was conducted to identify definitions of patient engagement and related terms in published literature (2006-2018). Definitions were extracted and qualitatively analyzed to identify themes and characteristics. A multistakeholder approach, including academia, industry, and patient representation, was taken at all stages. A proposed definition is offered based on a synthesis of the findings. Of 1821 abstracts identified and screened for eligibility, 317 were selected for full-text review. Of these, 169 articles met inclusion criteria, from which 244 distinct definitions were extracted for analysis. The most frequently defined terms were: “patient-centered” (30.5%), “patient engagement” (15.5%), and “patient participation” (13.4%). The majority of definitions were specific to the healthcare delivery setting (70.5%); 11.9% were specific to research. Among the definitions of “patient engagement,” the most common themes were “active process,” “patient involvement,” and “patient as participant.” In the research setting, the top themes were “patient as partner,” “patient involvement,” and “active process”; these did not appear in the top 3 themes of nonresearch definitions. Distinct themes are associated with the term “patient engagement” and with engagement in the “research” setting. Based on an analysis of existing literature and review by patient, industry, and academic stakeholders, we propose a scalable consensus definition of “patient engagement in research.” •The topic of patient engagement has become increasingly recognized in recent years as an important contribution to improved outcomes in the health research continuum. Until this point, the approach taken to defining and assessing engagement has not been systematic, with considerable differences among the definitions that do exist. Even fewer of those attempts at a definition have incorporated patient input.•Through a robust systematic review and qualitative-analysis process, a definition of patient engagement in research was generated that incorporates the most vital elements derived from our analysis. The aim of the definition is to meet the needs of, and support implementation by, a multistakeholder audience.•This proposed definition can act as a core statement of principles around which research decision making can be aligned. This includes the importance of inclusion, respect, and equality in the interactions between patients and researchers. Results of this work provide a concept against which the implementation of patient engagement in research can be evaluated and a starting point for further guidelines on “best practices” for patient engagement in the research process.A companion article from the study team's patient researchers discussing their experience working on this project and the definition's implications for patients will be in the July/August 2020 issue of ISPOR Value and Outcomes Spotlight.